The Use of Transposon Insertion Sequencing to Interrogate the Core Functional Genome of the Legume Symbiont Rhizobium leguminosarum - Perry, Benjamin J.; Akter, Mir S.; Yost, Christopher K. (Frontiers in Microbiology, 2016)
The free-living legume symbiont Rhizobium leguminosarum is of significant economic value because of its ability to provide fixed nitrogen to globally important leguminous food crops, such as peas and lentils. Discovery based research into the genetics and physiology of R. leguminosarum provides the foundational knowledge necessary for understanding the bacterium’s complex lifestyle, and to subsequently improve its application as a crop biological. Transposon insertion sequencing (INSeq) facilitates high-throughput forward genetic screening at a genomic scale to identify individual genes required for growth in a specific environment. In this study we applied INSeq to screen the genome of R. leguminosarum bv. viciae strain 3841 (RLV3841) for genes required for growth on minimal mannitol containing medium. Results from this study were contrasted with a prior INSeq experiment screened on peptide rich media to identify a common set of functional genes necessary for basic physiology. Contrasting the two growth conditions indicated that approximately 10% of the chromosome was required for growth, under both growth conditions. Specific genes that were essential to singular growth conditions were also identified. Data from INSeq screening on mannitol as a sole carbon source were used to reconstruct a metabolic map summarizing growth impaired phenotypes observed in the Embden-Meyerhof-Parnas pathway, Entner-Doudoroff pathway, pentose phosphate pathway, and tricarboxylic acid cycle. This revealed the presence of mannitol dependent and independent metabolic pathways required for growth, along with identifying metabolic steps with isozymes or possible carbon flux by-passes. Additionally, genes were identified on plasmids pRL11 and pRL12 that are likely to encode for functional activities important to the central physiology of RLV3841.